Relationship between serum antibodies and Taenia solium larvae burden in pigs raised in field conditions. - Cesar M Gavidia; Manuela R Verastegui; Hector H Garcia; Teresa Lopez-Urbina; Victor C W Tsang; William Pan; Robert H Gilman; Armando E Gonzalez; Cysticercosis Working Group in Peru (Public Library of Science (PLoS), 2013)
Serological tests have been used for the diagnosis of Taenia solium infection in pigs. However, those serological results do not necessarily correlate with the actual infection burden after performing pig necropsy. This study aimed to evaluate the Electro Immuno Transfer Blot (EITB) seropositivity with infection burden in naturally infected pigs.In an endemic area of Peru, 476 pigs were sampled. Seroprevalence was 60.5 ± 4.5% with a statistically higher proportion of positive older pigs (>8 months) than young pigs. The logistic model showed that pigs >8 month of age were 2.5 times more likely to be EITB-positive than ≤ 8 months. A subset of 84 seropositive pigs were necropsied, with 45.2% (38/84) positive to 1-2 bands, 46.4% (39/84) to 3 bands, and 8.3% (7/84) to 4+ bands. 41 out of 84 positive pigs were negative to necropsy (48.8%) and 43 (51%) had one or more cysts (positive predictive value). Older pigs showed more moderate and heavy infection burdens compared to younger pigs. In general, regardless of the age of the pig, the probability of having more cysts (parasite burden) increases proportionally with the number of EITB bands.The probability of being necropsy-positive increased with the number of bands, and age. Therefore, the EITB is a measure of exposure rather than a test to determine the real prevalence of cysticercosis infection.